Medicinal practices of sacred natural site: a socio-religious approach for successful implementation of primary healthcare services - Ray, Rajasri; Ray, Avik (Ethnobotany Research and Applications, 2020)
Background: Sacred groves are model systems that have the potential to contribute to rural healthcare owing to their medicinal floral diversity and strong social acceptance. Methods: We examined this idea employing ethnomedicinal plants and their application documented from sacred groves across India. A total of 65 published documents were shortlisted for the preparation of database and statistical analysis. Standard ethnobotanical indices and mapping were used to capture the current trend. Results: A total of 1247 species from 152 families has been documented for use against eighteen categories of diseases common in tropical and sub-tropical landscapes. Though the reported species are clustered around a few widely distributed families, 71% of them are uniquely represented from any single biogeographic region. The use of multiple species in treating an ailment, high use value of the popular plants, and cross-community similarity in disease treatment reflects rich community wisdom to explore and apply available natural resources. Conclusions: Building on the findings, integration of the tradition in primary healthcare policy especially in AYUSH (Ayurveda, Yoga, Naturopathy, Unani, Siddha and Homoeopathy) program has been recommended. This would embrace folk medicinal practices along with sustainable utilization of plant genetic resources in rapidly changing rural landscapes.